"From Enemies into Friends": Indians, Assimilation, and the Army, 1891–1897. Issue 3 (13th May 2020) - Krueger, David
Abstract: This article discusses the enlistment and service of specially organized "all-Indian Companies" within the U.S. Army from 1891 to 1897. Unlike previous units of Indian Scouts, these soldiers were organized, equipped, and trained as regulars, modeled on the success of Buffalo Soldier regiments and envisioned as a counterpart to the ethnically organized colonial forces of other imperial powers. These companies were inspired and sustained by arguments about Native Americans' unique military capabilities. More importantly, they served as vessels for programs of progressive reform and assimilation and as projections of an emerging American imperial identity. Simultaneously, the soldiers in these segregated formations leveraged their service to obtain practical economic and legal opportunities, as well as to support their arguments for more meaningful social and civic participation.